2015
DOI: 10.1152/ajpheart.00899.2014
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise training promotes physiological cardiac remodeling involving a set of microRNAs

Abstract: Fernandes T, Baraúna VG, Negrão CE, Phillips MI, Oliveira EM. Aerobic exercise training promotes physiological cardiac remodeling involving a set of microRNAs. Am J Physiol Heart Circ Physiol 309: H543-H552, 2015. First published June 12, 2015 doi:10.1152/ajpheart.00899.2014 hypertrophy is an important physiological compensatory mechanism in response to chronic increase in hemodynamic overload. There are two different forms of LV hypertrophy, one physiological and another pathological. Aerobic exercise induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
1
15

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(101 citation statements)
references
References 101 publications
0
85
1
15
Order By: Relevance
“…Interestingly, recent discoveries showed that circulating miR‐214 was up‐regulated in the early phase after AMI but then gradually decreased to near normal levels 163. Aerobic exercise training can alter the cardiac miRNA expression in physiological cardiac remodelling, such as miR‐1, miR‐150, miR‐21, miR‐122, miR‐126 and miR‐208 164. Mechanically, miR‐1 is enriched in cardiomyocytes and modulates myogenesis, cardiac development and hypertrophy, and miR‐208 is a cardiac‐specific miRNA expressed by introns of myosin heavy chains and involved in stress‐dependent cardiac growth and gene expression 165.…”
Section: Clinical Value Of Mirnas As New Biomarkers For Angiogenesis‐mentioning
confidence: 99%
“…Interestingly, recent discoveries showed that circulating miR‐214 was up‐regulated in the early phase after AMI but then gradually decreased to near normal levels 163. Aerobic exercise training can alter the cardiac miRNA expression in physiological cardiac remodelling, such as miR‐1, miR‐150, miR‐21, miR‐122, miR‐126 and miR‐208 164. Mechanically, miR‐1 is enriched in cardiomyocytes and modulates myogenesis, cardiac development and hypertrophy, and miR‐208 is a cardiac‐specific miRNA expressed by introns of myosin heavy chains and involved in stress‐dependent cardiac growth and gene expression 165.…”
Section: Clinical Value Of Mirnas As New Biomarkers For Angiogenesis‐mentioning
confidence: 99%
“…miR-1, miR-133, miR199a/b, miR-21, miR-23, miR-26, miR-29, miR-9, miR-98, and miR-499) have been shown to exert either a positive or negative influence on pathological cardiac hypertrophy (4 -6). Whereas several studies have recently profiled microRNA expression signatures in rat physiological hypertrophic hearts induced by swimming or treadmill training, it still remains unknown how dys-regulated miRNAs contribute to physiological hypertrophy (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…37 A study demonstrated the beneficial effects of aerobic exercise training on cardiac remodeling through its effect on certain miRNAs. 38 The effects included decreasing cardiac fibrosis by inhibiting collagen through upregulation of miR-29, inhibition of negative regulators of VEGF pathway. These effects of miR-126 in turn increase angiogenesis and modulation of the renin-angiotensin system by miRNAs-27a/ b and -143.…”
Section: Micrornas In Cardiovascular Diseasesmentioning
confidence: 99%
“…These effects of miR-126 in turn increase angiogenesis and modulation of the renin-angiotensin system by miRNAs-27a/ b and -143. 38 …”
Section: Micrornas In Cardiovascular Diseasesmentioning
confidence: 99%